Pengujian Black Box pada Aplikasi Penghitungan Parkir Swalayan ADA Menggunakan Teknik Equivalence Partitions - Nugraha, Bangkit Fajar; Aditama, Fahmi; Arrofi, Muhammad; Ahmad, Solakhul Umam; Yulianti, Yulianti (Teknik Informatika Universitas Pamulang, 2020)
To ensure that the application (software) Calculation of parking is no error then in need of testing to test the quality of the application. This application has problems with the calculation of the parking in the application, then the application will be tested by the Black Box method based on Equivalence where the application in the overall test is related to the use, benefit, and result of the utilization of such software. The parking application must be error-free, because if there is an error then it will be very detrimental to the self-service that use the parking application, specifically in terms of financial income. The Black Box-based method of Equivalence Partition tests the quality of the application by documenting the software testing which will look at the error in each form, and the errors will be divided into three models, errors, functions, data structures and interfaces. The results of this test, to ensure the quality of the free parking calculation application error by finding an accidental error in the parking calculation application.